Formulation and production of an additively manufactured Ti6al4v (Eli) composite with enhanced mechanical properties - Thamae, Masenate Seleso (Central University of Technology, 2024)
This research focused on the production of additively manufactured SiC/Ti6Al4V(ELI) composites with enhanced mechanical properties over those of the Ti6Al4V(ELI) alloy to increase the application of the alloy in the aircraft and automotive industries. The titanium alloy Ti6Al4V is mostly used in engineering applications due to its excellent combination of high specific strength, good fatigue properties and outstanding corrosion resistance. A limitation of titanium alloys is their poor abrasion resistance. This and other properties of these alloys were expected to be improved in this work by the addition of a strengthening phase consisting of silicon carbide (SiC) particles. These particles were used as reinforcement in the Ti6Al4V(ELI) matrix because of their excellent resistance to wear, high sublimation temperature relative to the melting temperature of Ti6A4V(ELI), specific stiffness, specific strength, hardness, and fracture toughness that are higher than those of the Ti6Al4V(ELI) matrix. Because SiC particles have a lower density (3.21 g/cm3) than Ti6Al4V(ELI) (density: 4.45 g/cm3) and a coefficient of thermal expansion (CTE) of 4.610-6/K, that is lower than the CTE of Ti6Al4V(ELI) of 8.610-6/K, the addition of SiC particles was expected to reduce the overall density and CTE of an SiC/Ti6Al4V(ELI) composite. When applied to the joints of aircraft structures, an SiC/Ti6Al4V(ELI) composite with a CTE closer to that of carbon fibre/epoxy resin composites (2.110-6/K) would minimize thermal- related buckling or separation at the interfaces. Furthermore, SiC particles with higher wear resistance than Ti6Al4V(ELI) would increase the wear resistance of an SiC/Ti6Al4V(ELI) composite. After mixing different volume fractions of Ti6Al4V(ELI) and SiC powder particles, single tracks were built from the mixtures to determine the optimum process parameters of laser power, scanning speed and energy density, all of which are known to influence the quality of built parts. Single tracks were built with different process parameter settings for each volume fraction of SiC (5 %,10 %,15 %, 20 %, 25 %, and 30 %) studied here. Top surface analysis of the tracks was done to identify the presence or absence of the keyhole and balling effects and to determine the degree of irregularity and discontinuity of the printed tracks. Thereafter, cross-sections of the tracks were prepared and examined in optical and/or scanning electron microscopes to determine the geometrical characteristics of single tracks of width, height, and depth of penetration into the substrate. The presence of continuous tracks with no balling, a lack of porosity, proper penetration, and dimensional stability in the generated tracks advised the selection of the best process parameters for each volume fraction. The best process parameters chosen for each SiC volume fraction were then utilized to create single layers at 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, and 110 μm hatch distances. Top surface examination of the layers was performed to investigate the continuity of tracks, balling or humping effect, surface roughness, and insufficient melting of the tracks. This was followed by cutting and preparation of cross-sections to investigate the degree of overlapping of tracks and the presence or absence of interior pores. Based on this analysis, the best hatch distances for each SiC volume fraction were selected for future use in the building of 3D specimens. Best single tracks were found at SiC volume fractions lying between 5 % and 25 %, inclusive, based on measured depth-to-width ratios of 0.5. At a SiC volume fraction of 30 %, the built tracks were observed to have poor penetration with depth-to-width ratios less than the optimum value of 0.5. The process parameters for these best single tracks were further used to build single layers where the hatch distances were varied from 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, to 110 μm for each SiC volume fraction from 5 % to 25 %, inclusive, while keeping all other process parameters, such as laser power, scanning speed and layer thickness constant, with the first two at the best- determined values. The best hatch distance for each volume fraction was then identified as the one that led to a printed layer with good overlapping, smooth surface topography and acceptable depth of penetration. It was recommended in this study that the mechanical properties of SiC/Ti6Al4V(ELI) composites might be increased at SiC volume fractions from 5 % to 25 %, inclusive, due to the fact that the best single tracks and single layers were obtained. Furthermore, the specimens to be built at the highest SiC volume fraction of 30 % might lead to decreased mechanical properties due to poor characteristics of produced tracks and single layers.
Master of engineering in Mechanical engineering
Keywords: additively manufactured SiC/Ti6Al4V(ELI); Ti6Al4V(ELI) alloy; titanium alloy